Interventionist Acquisition of Incidental Teaching Using Pyramidal Training via Telehealth. Issue 5 (September 2019) - Neely, Leslie; Rispoli, Mandy; Boles, Margot; Morin, Kristi; Gregori, Emily; Ninci, Jennifer; Hagan-Burke, Shanna
We investigated the effects of a telehealth pyramidal training package on participants' implementation of incidental teaching. A total of eight adults worked with eight children with autism. Coaches were first taught to implement incidental teaching and then taught subsequent interventionists. The training package consisted of an online module and delayed video-based feedback provided via videoconferencing. Following the telehealth training program, coaches and interventionists reached the preset performance criteria and implemented incidental teaching with high fidelity. All of the child participants increased mands above baseline levels. Results suggest that interventionists can be trained via telehealth in behavior analytic interventions.